Relating Meaningfully with the World: A Philosophical Perspective on School Leadership - Arrieta, Gilbert S. (Jayapangus Press, 2025)
Every teacher enters a classroom with a philosophy of education that serves as one’s moral and pedagogical principles in making teaching and learning happen meaningfully. Eventually, as the teacher grows in the teaching profession, he engages in mentoring and leading teachers and other stakeholders. Unconsciously, he creates personal school leadership philosophy that will be his guiding principles in leading the school. This study aims to find out the philosophy on school leadership of selected doctoral students and identify their leadership principles guiding them in carrying out their duties as current or future school heads. The findings will provide inputs in enhancing the graduate school core and specialization courses. Furthermore, the inputs will strengthen the development of graduate school students in becoming future-ready education leaders, expert practitioners and research scholars. Using qualitative content analysis as the methodology in this study, it found out that the participants’ school leadership philosophy is about positive and nurturing culture, being human, inspiration, empowerment and collaboration are evident. They believe that engaging in a meaningful relationship with the stakeholders is the most appropriate way in leading schools today. The findings validate the relevance today of classical and contemporary leadership theories on human relations, transformational leadership, empowerment, and synergy. Moreover, these may the leadership theories that must be emphasized in preparing and enhancing current and future school leaders.